1984
DOI: 10.1002/eji.1830141012
|View full text |Cite
|
Sign up to set email alerts
|

The immunoglobulin heavy chain variable region (Igh‐V) locus in the mouse. I. One hundred Igh‐V genes comprise seven families of homologous genes

Abstract: Seven families of Igh-V genes have been defined by Southern blot analysis of genomic DNA from eighteen inbred strains of mice. Each of twenty-four cloned Vh genes hybridized to one of seven nonoverlapping sets of Eco RI restriction fragments. These families contain from 2 to approximately 40 hybridizing fragments. From these data we estimate that the mouse Igh-V locus consists of one hundred Vh genes. Genes within a Vh family share greater than 80% sequence homology while the sequence homology between families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
237
2
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 511 publications
(248 citation statements)
references
References 39 publications
8
237
2
1
Order By: Relevance
“…To analyze these CDR3s, we first had to determine the germline sequences of the D genes in these NZB-derived mice. NZB mice had been reported to have a D locus of the Igh a haplotype by Southern blotting pattern (56), and we confirmed this by PCR amplification, cloning, and sequencing of germline D genes (data not shown).…”
Section: Rare D-d Rearrangements In Cdr3 Of Sle3/5 Congenic Mice and supporting
confidence: 74%
See 1 more Smart Citation
“…To analyze these CDR3s, we first had to determine the germline sequences of the D genes in these NZB-derived mice. NZB mice had been reported to have a D locus of the Igh a haplotype by Southern blotting pattern (56), and we confirmed this by PCR amplification, cloning, and sequencing of germline D genes (data not shown).…”
Section: Rare D-d Rearrangements In Cdr3 Of Sle3/5 Congenic Mice and supporting
confidence: 74%
“…In this study, we have found this V H gene in another lupus-prone strain, NZB, which is also Igh j for most of the V H locus (56). It is of interest that this novel gene was created by a process similar to V H replacement, i.e., invasion of a germline V H 7183 gene by an upstream V H 7183 germline gene.…”
Section: Germline V H Gene Created By V H Replacementmentioning
confidence: 81%
“…1 (18, 28, 35-37 (15)(16)(17) and the mouse Va repertoire of >100 (38) and substantially less than estimated pool sizes for VH or VK region genes, which contain on the order of 200-1000 genes (19)(20)(21) (18). Under less stringent washing conditions, 18 additional genes are detected with these probes (data not shown).…”
mentioning
confidence: 90%
“…First, there appear to be only 25-30 highly expressed mouse Va gene segments (15)(16)(17) contrasting with the several hundred to 1000 V gene segments in the V region light chain and heavy chain (VL and VH) immunoglobulin gene families (19)(20)(21). Second, the published mouse Vp gene segments fall into 16 V. subfamilies, as defined by nucleic acid hybridization with germ-line DNA on Southern blots, of which 13 contain just a single member (15)(16)(17)22).…”
mentioning
confidence: 99%
See 1 more Smart Citation